A multicentre, open-label, randomized comparative study of tigecycline versus ceftriaxone sodium plus metronidazole for the treatment of hospitalized subjects with complicated intra-abdominal infections - Towfigh, S.; Pasternak, J.; Poirier, A.; Leister, H.; Babinchak, T. (Clinical microbiology and infection, 2010)
Tigecycline (TGC) has demonstrated clinical efficacy and safety, in comparison with imipenem/cilastatin in phase 3 clinical trials, for complicated intra-abdominal infection (cIAI). The present study comprised a multicentre, open-label, randomized study of TGC vs. ceftriaxone plus metronidazole (CTX/MET) for the treatment of patients with cIAI. Eligible subjects were randomized (1:1) to receive either an initial dose of TGC (100 mg) followed by 50 mg every 12 h or CTX (2 g once daily) plus MET (1–2 g daily), for 4–14 days. The primary endpoint was the clinical response in the clinically evaluable (CE) population at the test of cure (TOC) assessment. Of 473 randomized subjects, 376 were CE. Among these, clinical cure rates were 70.4% (133/189) with TGC vs. 74.3% (139/187) with CTX/MET (95% CI –13.1 to 5.1; p 0.009 for non-inferiority). Clinical cure rates for subjects with Acute Physiological and Chronic Health Evaluation II scores ≥10 were 56.8% (21/37) with TGC vs. 58.3% (21/36) with CTX/MET. The microbiologic response was similar between the two treatment arms, with microbiological eradication at TOC achieved in 68.1% (94/138) of TGC-treated subjects and 71.5% (98/137) of CTX/MET-treated subjects. (The most frequently reported adverse events (AEs) for both treatment arms were nausea (TGC, 38.6% vs CTX/MET, 27.7%) and vomiting (TGC, 23.3% vs CTX/MET, 17.7%). Overall discontinuation rates as a result of an AE were 8.9% and 4.8% in TGC- and comparator-treated subjects, respectively. The results obtaned in the present study demonstrate that TGC monotherapy is non-inferior to a combination regimen of CTX/MET with respect to treating subjects with cIAI.